Snorkeling‐Based Fish Stock Assessment by Anglers—A Valuable Method for Managing Recreational Fisheries. (10th December 2018) - Pinter, Kurt; Lautsch, Erwin; Unfer, Günther; Hayes, Daniel S.
Abstract: Periodic assessment of harvested fish populations is essential for their sustainable management. A potential alternative to costly and resource‐intensive electrofishing estimates in clearwater streams is the noninvasive snorkeling method. To assess the utility of snorkeling for the angling community, we compared underwater fish counts carried out by novice snorkelers to state‐of‐the‐art electrofishing depletion estimates. Over two consecutive years, we sampled subadult and adult Brown Trout Salmo trutta and Rainbow Trout Oncorhynchus mykiss with both methods in a fourth‐order mountain stream. In each year, a new team of novice snorkelers collected the data. In total, 12 riffle, pool, and run habitats were sampled, and the homogeneity of abundance and size‐class distribution between the two methods was analyzed. Over both years, we could detect differences in 6 of 24 habitat × species configurations and in 10 of 72 habitat × species × size‐class configurations. Species‐specific behavioral traits and differences in the physical character of the habitats were responsible for a divergence in performance between the two methods. Overall, the observed effects were statistically interpreted as weak, as shown by local tests and the indicated low effect sizes. Snorkeling efficiency, however, remained affected by the effort and abilities of the team, as indicated by the year‐by‐year comparison. We conclude that in clearwater trout streams, snorkeling can be an appropriate substitute method for the widespread, autonomously organized angling community to gather data and build a sound foundation for fisheries‐related decision making, if limitations are considered.